Children with vesicoureteric reflux have joint hypermobility and occasional tenascin XB sequence variants - Tokhmafshan, Fatima (Can Urol Assoc J, 2020)
INTRODUCTION: To consider alternative mechanisms that give rise to a refluxing ureterovesical junction (UVJ), we hypothesized that children with a common heritable urinary tract defect, vesicoureteric reflux (VUR), may have a defect in the extracellular matrix composition of the UVJ and other tissues that would be revealed by assessment of the peripheral joints. Hypermobile joints can arise from defects in the extracellular matrix within the joint capsule that affect proteins, including tenascin XB (TNXB). METHODS: We performed an observational study of children with familial and non-familial VUR to determine the prevalence of joint hypermobility, renal scarring, and DNA sequence variants in TNXB. RESULTS: Most children (27/44) exhibited joint hypermobility using the Beighton scoring system. This included 15/26 girls (57.7%) and 12/18 boys (66.7%), which is a significantly higher prevalence for both sexes when compared to population controls (p<0.005). We found no association between joint hypermobility and renal scarring. Seven of 49 children harbored rare pathogenic sequence variants in TNXB, and two also exhibited joint hypermobility. No sequence variants in TNXB were identified in 25/27 children with VUR and joint hypermobility. Due to the observational design of the study, there was missing data for joint hypermobility scores in six children and for dimercaptosuccinic acid (DMSA) scans in 17 children. CONCLUSIONS: We observed a high prevalence of VUR and joint hypermobility in children followed within a tertiary care pediatric urology clinic. While mutations in TNXB have been reported in families with VUR and joint hypermobility, we identified only two children with these phenotypes and pathogenic variants in TNXB. We, therefore, speculate that VUR and joint hypermobility may be due to mutations in other extracellular matrix genes.